MEDICAL-BIOLOGICAL AND SOCIO-HYGIENIC RISK FACTORS IN THE DEVELOPMENT OF MOMENTUM TUMOR DISEASES - Toshmatova, G.A.; Erkinov, I.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The results of our study showed that the increase in the risk of developing benign breast tumors is inextricably linked with medical and biological factors. Among these factors, the most important were: late onset of menarche (at the age of 15-17); late becoming a mother; artificial termination of pregnancy; non-breastfeeding or short-term breastfeeding; the presence of concomitant diseases (inflammatory diseases of the genitals, diseases of the liver, biliary tract and gallbladder, various diseases of the thyroid gland); irregular course of sexual life; BMI above normal; hereditary predisposition and chest trauma. Early detection of risk factors contributes to the effective organization of preventive measures for the prevention of breast cancer. Keywords: mastopathy, menarche, breast cancer, risk factors.